AUTONOMOUS LEARNING STRATEGY TO IMPROVE LEARNERS’ WRITING SKILLS ON PACKAGE C PROGRAM IN PKBM BARITO BANJARMASIN - Achmad Aufa Najwan; Anisa Zahra; Ayudhia Sherani Firdaus; Sofia Lapuja; Yenni Mahrita; Md Noor Saper; Ciptro Handrianto (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2022)
The purpose of this study was to analyze whether the implementation of an autonomous learning strategy to learners of Package C in PKBM Barito Banjarmasin different after joining two cycles of learning based on the setting and level of learners` proficiency. This study applied qualitative descriptive method by using interview and observation for data collection. This study was divided into two cycles. The first cycle was the tutor introduced and explained the steps of autonomous learning, such as: finding topics, conducting library study, making drafts, writing essays, revising and scoring or self-evaluation. The second cycle, tutor explained in more detail how library search was performed as part of the autonomous learning process, especially the writing process. The results of study were (1) In the first cycle, less then 80% of learners who passed the specified criteria; and (2) In the second cycle, more than 80% passed the specific criteria in writing. Therefore, the cycle is stopped in phase 2 because the criteria for completeness have been achieved. It can be concluded that the application of an autonomous learning strategy to improve writing skills in organizing ideas is effective for learners.